Comparing the microstructure and mechanical properties of Bombyx mori and Antheraea pernyi cocoon composites - Guan, J; Zhu, W; Liu, B; Yang, K; Vollrath, F; Xu, J (Elsevier, 2016)
Silkworm cocoon material is a natural composite consisting of silk fibres and sericin glues. Both domestic and wild silkworms produce cocoons but with different functionality – one selected by man for textile manufacture whereas the other selected by Nature to provide damage-tolerant housing. To understand the structure-–property relationship of cocoons, we evaluated and compared the microstructure and mechanical properties of two representative cocoon walls. It appears that a “brittle and weak” composite is produced by domestic